Ligand-Controlled Regiodivergent Enantioselective Rhodium-Catalyzed Alkene Hydroboration - Bochat, Andrew J. (Angew Chem Int Ed Engl, 2019)
Regiocontrol in the rhodium-catalyzed boration of vinyl arenes is typically dominated by the presence of the conjugated aryl substituent. However, small differences in TADDOL-derived chiral monophosphite ligands can override this effect and direct rhodium-catalyzed hydroboration of β-aryl and -heteroaryl methylidenes by pinacolborane to produce either chiral primary or tertiary borated products selectively. The regiodivergent behavior is coupled with enantiodivergent addition of the borane. The nature of the TADDOL backbone substituents and that of the phosphite moiety function synergistically to direct the sense and extent of regioselectivity and enantioinduction. Twenty substrates undergo each reaction mode with regioselectivities reaching greater than 20:1 and enantiomer ratios reaching up to 98:2. A variety of subsequent transformations illustrate the potential utility of each product.